Aplikasi Asam Giberelin (GA) Alami dari Ekstrak Rebung untuk Meningkatkan Kualitas Buah Tomat (Lycopersicum esculentum Mill.) - NI NYOMAN ARYANINGSIH; NI NYOMAN ARI MAYADEWI; I PUTU DHARMA (Agrotrop : Journal on Agriculture Science, 2021)
The Application of Natural Gibberellic Acid (GA) from Bamboo Shoot Extract to Increase Quality of Tomato (Lycopersicum esculentum Mill). Tomato is a horticultural plant that has a lot of benefits. To increase the quality and productivity of tomatoes can be done by giving plant growth substances. This research aimed to find out the effect of natural gibberellic acid (GA) from bamboo shoot on the quality of tomatoes and to get the best natural gibberellic acid concentration from bamboo shoot to increase the quality and productivity of tomatoes. This research was designed using Randomized Block Design which consisted of 1 factor that is natural hormone concentration from bamboo shoot, with 5 treatments. Every treatment was repeated for 5 times. The standard of the treatment consisted of K0 as a control, K1 which was sprayed by 25% of bamboo shoot extract concentration, K2 which was squirted by sprayed by 50% of bamboo shoot extract concentration, K3 which was squirted by 75% of bamboo shoot extract concentration, and K4 which was sprayed by 100% of bamboo shoot extract concentration. The bamboo shoot was sprayed before the tomatoes’ flower blossomed. This research found that the application of bamboo shoot extract affected the quality of the tomatoes itself and reduced the number of seeds of tomato itself. In conclusion, the best concentration that can reduce the number of tomatoe’s seeds is the concentration of 75% (K3) compared to control one with 77%.